Process parameter optimization for 3D printing of photocurable resins in hydrogel media - Rociński, Mateusz; Pilch, Maciej (Chemical and Process Engineering: New Frontiers, 2026)
The aim of this work was to develop a low-cost 3D printing method operating in hydrogel environment and to find suitable process parameters and input materials. The proposed approach enables inexpensive fabrication of geometrically complex structures, including overhangs, without conventional support materials. A prototype device was created by modifying an FDM 3D printer with a syringe-based extrusion system, UVcuring module and dedicated vessel defining the printing workspace. Printing parameters were then optimized to achieve satisfactory resolution both in air & hydrogels. Preliminary experiments demonstrated that commercial photopolymer resins and hydrogels were inadequate for gel-based printing due to inappropriate rheological characteristics of both. Multiple 3D printing pastes and polymer gels of varied composition were prepared and examined through rheological and photorheological analyses, enabling selection of candidates for application testing. Using the optimized materials, beam specimens were printed and mechanically tested, with results compared to analogous samples produced via commercial DLP 3D printer. Among the hydrogel media, a guargum- based hydrogel containing 3% solids provided the most favorable support and rheology for DIW printing. The highest promise was shown by a paste formulated from a commercial ANYCUBIC resin with 5% amorphous silica, yielding prints of superior resolution, viscosity, adhesion and strength. Notably, beams printed in the guar-gum hydrogel showed significantly higher strength than DLP counterparts. Overall, the developed budget DIW technology in liquid media enables fabrication of simple, high-resolution, mechanically robust parts, with potential applications in bioprinting, delicate-material processing and complex geometry fabrication.